Analisis Perencanaan Penyusunan Paket Wisata Keliling Madura (PAK SAKERA) - Saputra, Aditya; Sri Rahayuningsih, Eni (Jurnal Etnik: Ekonomi-Teknik, 2023)
One way that can be done for the development of tourism in Madura is by cooperating with the four districts in Madura so that the development of the tourism sector can run optimally. After tourism development is underway, it is necessary to have the help of the private sector such as tour and travel agents as a vessel for fulfilling tourists visiting tourist destinations in Madura. The purpose of this research is to analyze the planning of the tour packages around Madura. Then analyze the extent to which the results have been carried out in the preparation of tour packages around Madura. The method used in this study is descriptive qualitative, using the SWOT analysis technique to determine the strengths, weaknesses, opportunities, and threats of the tour packages around Madura. The research locations are in 4 districts in Madura and Madura Indah Wisata Tour and Travel agents. The results found in the form of cooperation made by the 4 Regents in Madura became the first step as a guide so that the 4 regencies could work together to develop tourism potential in Madura. Provision of supporting facilities and infrastructure services is a step that needs to be provided in every tourist area. The preparation of tour packages around Madura is made carefully by selecting the best packages for tourists.